2016
DOI: 10.1016/j.celrep.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction with Ewing’s Sarcoma Breakpoint Protein EWS Defines a Specific Oncogenic Mechanism of ETS Factors Rearranged in Prostate Cancer

Abstract: Summary More than 50% of prostate tumors have a chromosomal rearrangement resulting in aberrant expression of an oncogenic ETS family transcription factor. However, mechanisms that differentiate the function of oncogenic ETS factors expressed in prostate tumors from non-oncogenic ETS factors expressed in normal prostate are unknown. Here we find that four oncogenic ETS, ERG, ETV1, ETV4, and ETV5, and no other ETS, interact with the Ewing’s sarcoma breakpoint protein, EWS. This EWS interaction was necessary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 50 publications
(75 reference statements)
7
82
1
Order By: Relevance
“…Transwell cell migration and clonogenic growth assays were performed in overexpression lines. Expression of flEWS induced significant cell migration and clonogenic growth compared to vector expressing cells, consistent with our previous work (Kedage et al, 2016). Additionally, ctEWS expression promoted these phenotypes to a similar extent as flEWS.…”
Section: Ntews Promotes Phenotypes Related To Oncogenesissupporting
confidence: 91%
See 3 more Smart Citations
“…Transwell cell migration and clonogenic growth assays were performed in overexpression lines. Expression of flEWS induced significant cell migration and clonogenic growth compared to vector expressing cells, consistent with our previous work (Kedage et al, 2016). Additionally, ctEWS expression promoted these phenotypes to a similar extent as flEWS.…”
Section: Ntews Promotes Phenotypes Related To Oncogenesissupporting
confidence: 91%
“…Both nuclear and cytoplasmic (Andersson et al, 2008), EWS, the protein encoded by EWSR1, has transcription-dependent and transcription-independent roles. We have previously reported that EWS can act as a transcriptional co-activator in prostate cancer (Kedage et al, 2016); other reported nuclear functions of EWS include the regulation of splicing and DNA damage repair (Dutertre et al, 2010;Gorthi et al, 2018;Paronetto et al, 2011). Sedimentation studies suggest that cytoplasmic EWS associates with dense, ribosome-containing fractions as well as lighter fractions that also contain the plasma membrane (Felsch et al, 1999).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, EWSR1-ETS is known to affect epigenetic programs [23,24] , splicing [25,26] , and metabolic activity [27] of EWS. Oncogenic fusions between ETS genes and transcriptional activators are not unique to EWS: in 50%-70% of prostate cancers, similar chromosomal rearrangements are found [28] . The breakpoint position varies, and commonly occurs between exons 7-11 for EWSR1 and exons 4-9 for FLI1, leading to variations in fusion types between patients with EWSR1-FLI1.…”
Section: Chromosomal Translocationsmentioning
confidence: 99%